PPPs in China: Does the Growth in Chinese PPPs Signal a Liberalising Economy?. Issue 5 (28th July 2020) - Jones, Lydia; Bloomfield, Michael J.
ABSTRACT: This study provides insight into the nature of public-private partnerships (PPPs) in China, a country that has invested more in PPPs than any other over the last two decades. It is puzzling that China, as a state-led economy, has turned to embrace PPPs. Pundits have taken this as evidence of a liberalising Chinese economy. However, our findings suggest that PPPs in China do not reflect a break from earlier, state-centric modes of governance; rather, the state essentially uses such partnerships as a mechanism to strengthen its own hand. We argue that the difference between how PPPs are being implemented in China compared to the West reflects differences in political economic contexts, both materially and ideologically. In both cases, the ambiguity surrounding the PPP model has been used to advance particular interests, serving as a reminder of both the ways in which power shapes the character of such policy tools and the differences in the relative power underpinning state-market relations in each context. By challenging mainstream interpretations of what PPPs are and what their proliferation means, studying the political economy of PPPs in a rising China further exposes the Western-centric nature of prevailing wisdom in political economy scholarship.